The trend and future projection of technology‐assisted total knee arthroplasty in the United States. Issue 1 (15th November 2022) - Lan, Yu‐Tung; Chen, Ya‐Wen; Niu, Ruijia; Chang, David C.; Hollenbeck, Brian L.; Mattingly, David A.; Smith, Eric L.; Talmo, Carl T.
Abstract: Background: As technology‐assisted surgery has boosted in the last decades, we aimed to investigate the factors affecting adoption and to predict the future utilization of technology among patients who underwent total knee arthroplasty (TKA). Methods: Patients underwent TKA in 2017–2019 in the MarketScan Database were included. Percentage of technology‐assisted surgery was calculated. Multivariable logistic regression models were performed to analyse the factors and make the prediction. Results: Of 112, 161 TKA procedures, 7.2% were technology‐assisted. The proportion of technology‐assisted TKA is expected to reach 50% by 2032. The West showed the highest proportion of technology‐assisted TKA (12.3%), while the South had the lowest (5.7%). Over time, the Midwest showed the greatest increase in technology adoption (OR = 1.26 compared to the Northeast, 95% CI [1.15, 1.38]). Conclusions: Technology adoption rate of TKA will continue to increase for the next 20 years in the United States with a slight geographical variation.